Intensified Infliximab Induction is Associated with Improved Response and Decreased Colectomy in Steroid-Refractory Paediatric Ulcerative Colitis. (23rd January 2019) - Church, Peter C; Ho, Shaun; Sharma, Ajay; Tomalty, Diane; Frost, Karen; Muise, Aleixo; Walters, Thomas D; Griffiths, Anne M
Abstract: Background: Infliximab pharmacokinetics in steroid-refractory [SR] ulcerative colitis [UC] suggest a need for higher dosing, but data concerning efficacy of intensification in this setting are lacking in children and inconsistent overall. Methods: Paediatric patients [ N = 125] treated with infliximab for SR or steroid-dependent UC were retrospectively reviewed. Outcomes [clinical response and remission, colectomy, mucosal healing, safety] with standard vs intensified induction [mean induction dose ≥7 mg/kg or interval ≤5 weeks between doses 1 and 3] were compared. Results: Among 125 patients [median age 14 years, median UC duration 0.7 years, 74 SR], 73 [58%] received standard induction and 52 [42%] received intensified induction. Overall, 73 [58%] achieved remission (judged by physician global assessment [PGA] and paediatric UC activity index [PUCAI]≤10]. Among patients in remission, 7 [10%] experienced secondary loss of response by a median of 0.7 [IQR 0.4–1.0] years. Of the 74 SR patients, 17 [23%] underwent colectomy, and of the 51 steroid-dependent patients, 12 [24%] underwent colectomy. Intensified induction in SR patients was associated with a higher chance of remission (hazard ratio [HR] 3.2, p = 0.02) and a lower chance of colectomy [HR 0.4, p = 0.05], but did not improve outcomes in steroid-dependent patients. During follow-up, 46/73 [63%] patients in remission had regimen individualization, with similar rates of return to standard dosing after 1 year between those with initial intensified or standard induction. Follow-up endoscopy, performed in 35/73 patients in remission, demonstrated mucosal healing for 66%. Adverse events were rare, despite use of intensified regimens. Conclusions: These data suggest a benefit from intensified infliximab induction specifically among children with steroid-refractory UC. Prospective studies comparing dosing regimens and incorporating therapeutic drug monitoring should be undertaken.